An End to China's Imbalances? - Ahuja, Ashvin (IMF Working Papers; Working Paper ;, 2012)
Global imbalances have been a central theme of the international economic policy debate for much of the last decade, prompted by large and sustained current account deficits in the U.S. and counterpart surpluses in China, Germany, and among many of the oil producers. This paper focuses on the current state of the external imbalance in China, examining the factors underlying the post-2008 drop in China's current account surplus and analyzing the prospects for the external surplus going forward. The paper finds that China's current account surplus should remain modest in the coming years. However, despite the fact that China's medium-term current account is likely to stay below its pre-crisis range, it is too early to conclude that "rebalancing" has been truly achieved in China. While imbalances do not currently seem to be manifesting themselves as a feature of China's external accounts, the evidence increasingly points to a rising domestic imbalance as growth becomes increasingly dependent on very high levels of investment.